Toward a carbon neutral path: exploring the impact of digital economy on carbon neutrality performance - Meiling Wang; Yuying Wang (International Journal of Climate Change Strategies and Management)
Purpose – The pursuit of carbon neutrality is a deliberate and systematic effort in response to the severe consequences of climate change. The emerging digital economy provides a novel pathway for advancing carbon neutrality. This study specifically aims to investigate the relationship between the digital economy and carbon neutrality performance, utilizing interprovincial data from China spanning the period from 2011 to 2021. Design/methodology/approach – To examine the impact of the digital economy on carbon neutrality performance, this paper employed two models: a one-way fixed effects model and a mediated effects model, using interprovincial data from China spanning the period from 2011 to 2021. Findings – The findings demonstrate that the enhancement of carbon neutrality performance is positively affected by the digital economy, particularly in western and central China, regions characterized by lower levels of marketization and higher financial pressures. Mechanism analysis reveals that improvements in industrial structure, consumption patterns and economic development, driven by digital economy growth, further improve carbon neutrality performance. Practical implications – This study provides critical policy insights to support achieving the “dual-carbon goal” and promote high-quality development in the national economy. Moreover, it enriches the discussion on the factors affecting carbon neutrality and deepens our understanding of how the digital economy impacts carbon neutrality performance. Originality/value – To the best of the authors’ knowledge, this study is the first to examine how the digital economy affects carbon neutrality performance in China from 2011 to 2021.